Surgical approach to atypical localization of osteochondroma (Boletin Médico de Postgrado, 2024)
Osteochondromas represent the most common primary bone tumors. So far, there have been no recent reports of osteochondroma in the Venezuelan population and even less of atypical localization. We present a clinical case of a 29-year-old female patient who consulted for progressive increase of volume in the posterior area of the left knee accompanied by pain and functional limitation for walking of 10 years of evolution. Plain radiography of the left knee and magnetic resonance imaging confirmed the presence of a space-occupying lesion in the popliteal region originating from the head of the fibula. The preoperative biopsy reported osteochondroma without malignancy. She underwent surgery with a wide posterior approach to the knee with an S-shaped incision with total exposure of the tumor and dissection of the popliteal artery, popliteal vein, tibial nerve and peroneal artery, with immobilization of the left lower limb using an inguino-malleolar splint. The patient had an uncomplicated postoperative period, with radiographic results 9 days after surgery showing total exeresis of the tumor and biopsy results of the surgical specimen of osteochondroma with no evidence of malignancy. The patient continues with satisfactory evolution and progressive reintegration to her work and social activities. The recommended treatment of choice for symptomatic atypical osteochondromas is surgical resection and follow-up due to the possibility of malignancy.
Keywords: neoplasm, bone tissue; osteochondrosis; knee; biopsy; orthopedic procedures